RACIAL DISCRIMINATION IS A MAJOR SOCIAL ISSUE IN INDIA WHICH HAS RESULTED IN COMMUNAL VIOLENCE AMONG DIFFERENT CASTE AND RELIGION - Dr.Sumanta Bhattacharya; Bhavneet Kaur Sachdev (Galaxy International Interdisciplinary Research Journal, 2021)
Every day we get to hear cases reported on crime against Dalit , SC and ST in India , in fact this COVID-19 has shown us the sad reality of how badly the North-East region of India is treated because of their physical appearance across the country , where as half of the cases go unreported , in fact this communal riots between the Hindu and Muslims have their roots in racism and ethnic discrimination. The value of white skin and reject of dark skin people have ruined up the life of many and some have even committed suicide because of the mental torture and the fear of not being accepted as part of the society . We have lack of social security , if we see a couple you gets married not belonging from the same caste they are either burn alive or either of a one is killed , it is wrong in India to many a person not belonging to your caste . These social stain has also hampered the economic growth of the society where qualification and talent have been suppress , caste and skin colour has been given utmost importance . We need to bring an end to this racial discrimination before its results in internal war between different castes and for strict laws and regulation along with bring a progressive and liberal attitude among the people of all generation and promote harmony and peace .